The Nuevas aventuras de Robinson Crusoe - Defoe, Daniel, 1661?-1731. (Wheaton, Ill. : Tyndale, 1999)
Presents the complete text of Daniel Defoe's "The Farther Adventures of Robinson Crusoe," which chronicles Crusoe's travels through China, Russia, Siberia, and back to the island on which he was shipwrecked years earlier. Includes footnotes, illustrations, an introductory essay, and discussion questions.
Includes bibliographical references.
"Works by or attributed to Daniel Defoe": p. xlix-lxiii.
Young Adult
Young Adult.
Keywords: Crusoe, Robinson (Fictitious character) -- Fiction; Voyages and travels -- Fiction; Crusoe, Robinson (Fictional character) -- Fiction; Voyages and travels -- Fiction; Asia -- Description and travel -- Fiction; Asia -- Description and Travel -- Fiction